Polydentate hydrazones as multitasking catalysts in visible-light-induced coupling reactions of amines. Issue 4 (4th January 2023) - Wang, Ganghu; Zhang, Jianhua; Hu, Legen; Wang, Jiaquan; Zhu, Chunyin
Abstract : A Cu/hydrazone catalyst has been applied in the coupling reactions of anilines for the synthesis of diarylamines and azobenzenes. Abstract : A Cu/hydrazone catalyst has been applied in the coupling reactions of anilines for the synthesis of diarylamines and azobenzenes. The copper complex that is formed in situ plays a double duty by harnessing photon energy as a photocatalyst and then by catalysing organometallic elementary steps as a transition metal catalyst. By the selection of hydrazones and bases, the reaction selectivity of aniline can be tuned between homo-coupling and its cross-coupling with arylboronic acid, exhibiting the great potential of such hydrazones in organic synthesis.